Syllabus Development of Language Editing Courses Indonesia Based on Information and Communication Technology Integrated XXI Century - Oktaviani, Reni; Ansoriyah, Siti; Purbarani, Etsa (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The background of this research is about a pandemic that has changed learning patterns from face-to-face to face-to-face. This causes the syllabus that existed before the pandemic to adapt to current conditions. In addition, this syllabus applies a project-based learning model and case studies. The purpose of this research is to explain and develop the syllabus of the Indonesian Language Editing course based on integrated Information and Communication Technology (ICT) in the XXI century. This research uses research and development. The stages in this research, namely: first, explain the process of developing the syllabus for the integrated ICT-based Indonesian language editing course in the XXI century. Second, developing a syllabus for the XXI century integrated ICT-based Indonesian Language Editing course. Data collection techniques were obtained through tests and non-tests in the form of observations, questionnaires, and documentation and then processed using content analysis techniques. Based on this, the development of an integrated ICT-based syllabus in the XXI century was applied to level IV students of the Indonesian Language and Literature Education Study Program to obtain effective learning outcomes in the Indonesian Language Editing course.